Brachistochrone Bowl‐Inspired Hybrid Nanogenerator Integrated with Physio‐Electrochemical Multisensors for Self‐Sustainable Smart Pool Monitoring Systems. Issue 14 (26th January 2023) - Maharjan, Pukar; Bhatta, Trilochan; Hui, Xue; Pradhan, Gagan Bahadur; Song, Hyesu; Shrestha, Kumar; Park, Jae Yeong
Abstract: Maintaining clean and fresh pool water requires regular monitoring and treatment. However, the employed methods are manual, complex, and time‐consuming. Herein, a self‐sustainable autonomous smart pool monitoring system (SPMS) that can monitor various physio‐electrochemical properties of the pool water in real‐time without requiring external power is proposed. SPMS includes an electromagnetic generator inspired by the novel brachistochrone bowl which harvests energy from random motion (peak power 72 mW at 4 Hz and 0.5 g) and supplies the wireless transmission unit and the highly sensitive multifunctional sensor unit (MSU) including pH (−60.71 mV pH −1 ), temperature (2.5 Ω °C −1 ), chloride (0.355 mV ppm −1 ; <250 ppm), conductivity (3.25 × 10 −5  µS ppm −1 ), and wave motion (1.27 V Hz −1 ). The fabricated MSU has adequate sensitivity and accuracy to detect minor variations in the water quality for indoor and outdoor environments. Finally, the smart pool monitoring application of the SPMS is demonstrated in real‐time by acquiring the sensor data and wirelessly transmitting it to the custom‐developed mobile application utilizing harvested energy. Combining energy harvesting and water quality sensing, the free‐floating completely isolated SPMS device demonstrates a portable, freestanding, wireless, autonomous, and self‐powered pool monitoring system for maintaining a hygienic and safe swimming environment. Abstract : A novel brachistochrone bowl‐shaped hybrid nanogenerator integrated with a physio‐electrochemical multifunctional sensing platform is demonstrated for a self‐sustainable wireless smart pool water monitoring system. The generator harvests sufficient electricity at a low frequency while the fabricated sensors have excellent sensitivity, accuracy, and selectivity making the system suitable for wireless monitoring of pool water in real‐time in both indoor and outdoor swimming environments without requiring external power.